Quality Management Systems in the Food Industry. - Baert, K., ....-; Devlieghere, Frank, 1968-; Jacxsens, L., ....-; Debevere, Johan, 1942- (Gent : Universiteit Gent, 2005)
This book contains an overview of qualitiy management systems in the food industry and agruculture. The second part deals with food legislation. Then, there is a part about good manufacturing practices and prerequisite programs. Finally, the book has a part about hazard analysis and critical control points.
Keywords: Voedselhygiëne; Voedselveiligheid